Pengaruh Total Solid dan Perbandingan Bahan Baku dengan Inokulum terhadap Produksi Biogas dari Jerami Jagung - Gita Indah Budiarti; Lukhi Mulia Shytophyta; Dika Fajariyanto; Yusuf Eko Nugroho (CHEMICA: Jurnal Teknik Kimia, 2018)
The effect of total solid (TS) content and feedstock/inoculum (F/I) ratioÂ  on biogas production from corn stover by solidâ€state anaerobic digestion (SSâ€AD) were studied. At a F/I ratio of 2, conversion of corn stover under room temperature resulting in higher biogas yield. SSâ€AD performed as expected at the TS content of 20%, 22%, 24%. The highest biogas yield of 200 L kgâ€1 volatile solids (VS) was obtained at TS content of 22%, F/I ratio of 2.